Density and spatial distribution of Atta sexdens rubropilosa and Atta laevigata colonies (Hym., Formicidae) in Eucalyptus spp. forests - Ramos, Vania M. [UNESP]; Forti, Luiz C.; Andrade, Ana Paula P.; Noronha, Newton C.; Camargo, Roberto Da Silva (California State University, 2008)
The present study determined the density and spatial distribution of nests of the leaf-cutting ants Atta sexdens rubropilosa and A laevigata in an area of Eucalyptus spp. forest. The research was accomplished between 05/2000 and 11/2001, on a farm located in Botucatu, SP, inside Area 19, with approximately 56,000 m(2), without a history of control for at least 3 years. The operation was accomplished by theodolite. The collected data facilitated the making of a working area map, containing the exact location of all the nests. For each one of the nests, its identification, codification, measurements and location in relation to the closest border of the area were also obtained. The density of nests found in the study area was 10 nests/ha, considering the two species present. The data obtained also demonstrated the tendency of the nests to concentrate in strips located closer to the borders of the area. Regression analysis revealed the existence of a negative correlation between distance from the borders and the number of colonies. Analysis of spatial distribution of colonies in the area also showed that the distribution is aggregated, being adjusted to a model of a negative binomial distribution. The results showed that spatial distribution of colonies in the studied area was concentrated in the strips closer to the borders of the area, which would allow, in this case, good pest control efficiency without the need of traversing the total area.
Keywords: leaf-cutting ants; forest management; chemical control; spatial distribution